Nazwy telewizyjnych programów sportowych z komponentem wartościującym (na przykładzie stacji Canal+ Sport) - KATARZYNA BURSKA (Stylistyka)
The purpose of this article is to look at the names of TV sports programmes through the prism of values and valuation. Research methods developed both in onomastics and axiology were used. An attempt was made to answer the questions: What axiologically characterized elements are the components of the names of sports programs? What values do their creators refer to? Which names – for their direct or indirect values – are more common? The study is based on the typology of ultimate values proposed by Jadwiga Puzynina. The research basis is the names of television programs on the Canal+ Sport Channel. The analyzed medionyms most often include references to vital and feeling values. Much less frequently the creators of medionym refer to cognitive, customary or moral values. Few names contain a value-primar component, while the vast majority are definitional or connotative value words. In the studied propria, value measures from different levels of language are used. Positive axiologization dominates.